“Candidatus Thermonerobacter thiotrophicus,” A Non-phototrophic Member of the Bacteroidetes/Chlorobi With Dissimilatory Sulfur Metabolism in Hot Spring Mat Communities - Thiel, Vera; Garcia Costas, Amaya M.; Fortney, Nathaniel W.; Martinez, Joval N.; Tank, Marcus; Roden, Eric E.; Boyd, Eric S.; Ward, David M.; Hanada, Satoshi; Bryant, Donald A. (Frontiers in Microbiology, 2019)
In this study we present evidence for a novel, thermophilic sulfate-reducing bacterium, tentatively named ‘Candidatus Thermonerobacter thiotrophicus’, which is affiliated with the Bacteroides/Ignavibacteria/Chlorobi superphylum. Dissimilatory sulfate reduction (DSR) is an important and ancient metabolic process for energy conservation with global importance for geochemical sulfur and carbon cycling. Characterized sulfate-reducing microorganisms (SRM) are found in a limited number of bacterial and archaeal phyla. However, based upon highly diverse environmental dsrAB sequences, a variety of uncultivated and unidentified SRM must exist. The recent development of high-throughput sequencing methods allows the phylogenetic identification of some of these uncultured SRM. In this study, we identified a novel putative SRM inhabiting hot spring microbial mats that is a member of the OPB56 clade (Ca. Kapabacteria) within the Bacteroidetes/Chlorobi superphylum. Partial genomes for this new organism were retrieved from metagenomes from three different hot springs in Yellowstone National Park, USA, and Japan. Supporting the prediction of a sulfate-reducing metabolism for this organism during period of anoxia, diel metatranscriptomic analyses indicate highest relative transcript levels in situ for all DSR-related genes at night. The presence of terminal oxidases, which are transcribed during the day, further suggest these organisms might also perform aerobic respiration. The relative phylogenetic proximity to the sulfur-oxidizing, chlorophototrophic Chlorobi further raises new questions about the evolution of dissimilatory sulfur metabolism.